The genus Potamolithus Pilsbry, 1896 (Gastropoda: Tateidae) on the Somuncurá Plateau, Patagonia, Argentina - Lucía, Micaela de (2017)
The genus Potamolithus (Gastropoda: Tateidae) is endemic to South America where it is distributed mainly in the Ribeira, Itajaí-açú and Jacuhy Rivers in southern Brazil and the Uruguay River, part of the Paraná and Río de la Plata drainage systems. An exception to the pattern of distribution is Potamolithus valchetensis Miquel, 1998, which is endemic to the Valcheta Stream, Somuncurá Plateau, Patagonia, Argentina. Here we provide a review of Potamolithus from this plateau based on new samples and review of material deposited in collections. A new species, Potamolithus elenae, is named. The shell, head-foot, penis, pallial organs and radula are described. Differences between the new species and P. valchetensis include details in the shell, radula, body pigmentation and penis. A phylogeny using mitochondrial gene cytochrome c oxidase subunit I is provided which shows that Potamolithus is related to species in New Caledonia (Australasia), suggesting that the Tateidae has a Gondwanan distribution.